Are biases contagious? The influence of communication on motivated beliefs - Andreas Grunewald; Victor Klockmann; Alicia von Schenk; Ferdinand von Siemens (University of Würzburg, Department of Economics, 2024)
This paper examines the potential reinforcement of motivated beliefs when individuals with identical biases communicate. We propose a controlled online experiment that allows to manipulate belief biases and the communication environment. We find that communication, even among like-minded individuals, diminishes motivated beliefs if it takes place in an environment without previously declared external opinions. In the presence of external plural opinions, however, communication does not reduce but rather aggravates motivated beliefs. Our results indicate a potential drawback of the plurality of opinions-it may create communication environments wherein motivated beliefs not only persist but also become contagious within social networks.
urn:nbn:de:bvb:20-opus-348936
Keywords: C91; C92; D83; 330; Belief bias; Social interaction; Motivated beliefs